ESRA19-0087 The effect of epinephrine as an additive to ropivacaine during ultrasound-guided interscalene brachial plexus block. (30th August 2019) - Kim, D; Jeong, JS; Park, SJ; Choi, D; Ko, JS
Abstract : Background and aims: Adding epinephrine to ropivacaine has shown various prolonging effects on the duration analgesia, and its potential effect on decreasing the local anesthetic volume also remains unclear. We aimed to investigate the superiority of epinephrine as additive to ropivacaine on the duration of analgesia after ISBPB and to evaluate the noninferiority of sensory blockade duration after reduction of the ropivacaine combined with epinephrine. Methods: In this prospective study, the duration of analgesia (time to first pain at surgical site) after shoulder surgery was compared as a primary outcome. a total of 65 patients who underwent shoulder arthroscopy under ISBPB with general anesthesia were included. Participants were randomly allocated into three groups: Group R20 ( n = 9, 0.5% ropivacaine 20 ml + normal saline 5 mcg/ml), group R10E ( n = 28, 0.5% ropivacaine 10 ml + epinephrine 5 mcg/ml), or group R20E ( n = 28, 0.5% ropivacaine 20 ml + epinephrine 5 mcg/ml). Duration of analgesia was recorded. Results: The mean (SD) analgesic durations were 562 (134) min, 470 (76) min, and 488 (109) min in R20E, R20, and R10E groups, respectively. the duration of analgesia in the Group R20E was increased by 16% compared to Group R20 ( P = 0.017) and by 13% compared to Group R10E ( P = 0.027). No participants experienced any adverse effect including neurologic sequelae. Conclusions: Addition of epinephrine to ropivacaine prolonged the duration of analgesia after interscalene BPB in patients undergoing shoulder arthroscopic surgery.